Franchising in Serbia: Trends and perspectives - Milica Stanković; Jovana Džoljić; Vladimir Popović; Tiana Anelković (UTMS Journal of Economics, 2023)
Considering the great importance of franchising for economic development at the global level, the research of this business concept is very important for its further improvement. Despite the existence of a number of studies on the topic of franchising, this area is still insufficiently researched, especially in the Republic of Serbia. One of the biggest problems in the field of franchising in the Republic of Serbia is insufficient information about franchising as a business concept and internationalization strategy. Therefore, it is necessary to promote this concept as a chance for successful business, both within the borders of our country and on the international market. The aim of the paper is to point out the importance of franchising as a business model, with special reference to the development and importance of franchising in the Republic of Serbia and recommendations for the improvement of the franchise sector.
Keywords: M19; M21; 330; franchising; franchisor; franchisee; Serbia; internationalization